Rallying forces ; OPM blues ; Ivy Violan [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Tackles the protest march from Batac, Ilocos Norte to Manila that ended in violent dispersal. Interview with record artists and producers about original Pilipino music. An interview with Ivy Violan.